Inclusão e acessibilidade no centro de Bernardino de Campos - Costa, Luiz Gustavo Scarano [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The topics related to inclusion and accessibility are important for society, as they support the discussion of the improvement the living conditions for disadvantaged and/or disabled people. In this context the aim of this study was to discuss the possibility of improving accessibility for people with disabilities in Quintino Bocaiúva Square in Bernardino de Campos / SP. During the development of the study, it was necessary to research the most important concepts related to inclusion and accessibility in Brazil and the historical context in which they were inserted, besides to search for alternatives for the proposed question. By means of interviews and fieldwork, it was possible to identify the accessibility points and the adaptation requirements in the square. After data collection, a set of tactile maps was elaborated using Tactile Cartography techniques that will be able to help users of this space. The result of this research was a reflection on the importance of seeking alternatives for the effective inclusion of all citizens of the Bernardino de Campos, regardless of the presence or not of some disability

Temas relacionados a Inclusão e Acessibilidade são importantes para a sociedade, pois auxiliam na discussão da melhoria das condições de vida para pessoas menos favorecidas e/ou com deficiência. Neste contexto o objetivo deste trabalho foi discutir a possibilidade de melhorar a acessibilidade para pessoas com deficiência na Praça Quintino Bocaiúva em Bernardino de Campos/SP. No desenvolvimento do trabalho foi necessário pesquisar os conceitos mais importantes relacionados à inclusão e a acessibilidade no Brasil e o contexto histórico em que foram inseridos, além de buscar alternativas para a questão proposta. Por meio de entrevistas e trabalho de campo foi possível identificar os pontos de acessibilidade e a necessidade de adaptações na praça. Após esse levantamento foi elaborado um conjunto de mapas táteis utilizando as técnicas da Cartografia Tátil que poderão auxiliar os usuários deste espaço. O resultado da pesquisa foi uma reflexão sobre a importância de se buscar alternativas para a efetiva inclusão de todos os cidadãos de Bernardino de Campos, independe da presença ou não de alguma deficiência
Keywords: Integração social; Acessibilidade; Cartografia